Trajetória acadêmica de estudantes com transtorno do espectro do autismo e deficiência intelectual no ensino superior: similaridades e diferenças - Fernanda da Silva Pires (2023)
Autism Spectrum Disorder (ASD) has a cause that is still little known and is characterized by difficulties in socialization and communication, with restricted and repetitive patterns of some behaviors. Together, Law No. 12.764/12, which establishes the National Policy for the Protection of the Rights of Persons with ASD, guaranteeing them all the rights of other people with disabilities, and the National Policy on Special Education from the Perspective of Inclusive Education (2008) provide the exercise of citizenship and the right to education at all levels of education. Prior to 2012, people with ASD were not considered people with a disability and are likely to have entered University as a student with an intellectual disability (ID) or in broad competition. After the National Policy of the Person with ASD, they were able to declare themselves with this Disorder. This study aimed to know the academic trajectory of students with ASD, enrolled in higher education at the Federal University of Minas Gerais and to compare these trajectories with those of students with ID at the same institution, to aspire forsimilarities and differences. This is a retrospective cohort study, using a secondary database on undergraduate students with disabilities, referring to the period 2012 to 2020, made available by the Directory of Registration and Academic Control of the University. After statistical, descriptive, and inferential analysis, students with ASD and ID were characterized; tests were performed to compare the average between the two groups, comparisons and correlations, witha significance level of 5% for all analyses. It was possible to identify the similarities of thetrajectory and profile of these students, such as: male prevalence, brown color, from public schools, attended high school, attended the University in the same shift (day), same period ofacademic occurrences for partial and total trances, in addition to completing their studies within the period. Differences between groups were: higher scores on the National High School Examination (ENEM) in the group of students with ASD; the time between leaving high schooland entering the University is shorter for students in the ASD group; the entry age is late for students with ID, the greatest demand for the service of the Accessibility and Inclusion Center (NAI) is by the group with ASD and the areas of knowledge are also different (ASD – Healthand Exact and Earth Sciences; ID - applied social). By separating the academic trajectories of students with ASD and ID, it was possible to understand the paths of these two groups differently, helping to identify them from access to permanence of both groups. The inclusive practice in Higher Education Institutions is recent, and it is necessary to guarantee access conditions, together with the planning of actions and support services that guarantee the qualified permanence of students in academic spaces and activities.